2016
DOI: 10.1016/j.joca.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of an anti-ADAMTS-5 antibody on joint damage and mechanical allodynia in a murine model of osteoarthritis

Abstract: Objective The primary goal of this study was to test the disease-modifying effect of blocking a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-5 with a neutralizing monoclonal antibody (mAb) starting 4 weeks after destabilization of the medial meniscus (DMM) in the mouse. We also investigated whether ADAMTS-5 blockade reversed mechanical allodynia and decreased monocyte chemoattractant protein (MCP)-1 production by dorsal root ganglia (DRG) cells. Methods Ten-week old male C57BL/6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 33 publications
(51 reference statements)
7
76
0
Order By: Relevance
“…As previously reported, we confirmed that the withdrawal threshold was unchanged in naïve mice, while DMM mice developed mechanical allodynia by week 4, which was maintained for the 16-week follow-up period after surgery [6, 38] (data not shown). Four, 8, and 16 weeks after DMM or 8 weeks after sham surgery, we assessed the L4 level of the dorsal horn for Iba1 immunoreactivity, a marker for microglia, and assessed the number of Iba1-ir cells that had an activated morphology (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As previously reported, we confirmed that the withdrawal threshold was unchanged in naïve mice, while DMM mice developed mechanical allodynia by week 4, which was maintained for the 16-week follow-up period after surgery [6, 38] (data not shown). Four, 8, and 16 weeks after DMM or 8 weeks after sham surgery, we assessed the L4 level of the dorsal horn for Iba1 immunoreactivity, a marker for microglia, and assessed the number of Iba1-ir cells that had an activated morphology (Fig.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, joint damage after DMM surgery progresses very slowly: during the first 8 weeks, cartilage degeneration and osteophyte formation are mild to moderate, while joint damage accelerates between weeks 8 and 16 [38, 49]. Concomitantly with progressive joint damage, DMM mice develop progressive mechanical allodynia [21, 23], which appears 4 weeks after surgery and is maintained for 16 weeks, whereas sham surgery results in a short-lived mechanical allodynia at 4 weeks [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The DMM model is a well-defined joint instability-induced OA model, and has been widely used to study the roles of various molecular signaling pathways in PTOA. 1317 After DMM, mild-to-moderate histological OA signs usually start at 4 weeks, and become significant at 8–12 weeks. 12 To evaluate the chronological changes in the nanomechanical properties of cartilage, we performed atomic force microscopy (AFM)-based nanoindentation on femoral condyle cartilage surfaces from 3 days to 12 weeks after DMM, and compared the results against joint morphological changes detected by histology and μCT.…”
Section: Introductionmentioning
confidence: 99%
“…By 2–4 weeks after DMM surgery, mild cartilage lesions, subchondral bone sclerosis, and osteophytes are evident (15, 1921), while synovitis has recently been reported to peak during this time as well (16). As the disease progresses, cartilage lesions worsen, osteophytes mature, and synovitis resolves, but not completely (16, 22).…”
Section: Introductionmentioning
confidence: 99%